Characteristic Description of Stunting Toddler in North Luwu Regency in 2023 - As Salam N., Siti Nuraisyah Aulia; Arfah, Arni Isnaini; Khalid, Nur Fadhillah; Bamahry, Aryanti R.; Namirah, Hanna Aulia (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Stunting is a state of persistent unhealthiness caused by a lack of food intake over a long period of time due to nutritional intake that is not in accordance with healthy needs. Genetic factors, breastfeeding (breast milk), low birth length dan low birth weight (LBW), immunization status, history of disease are factors related to the occurrence of stunting children. The aim of this research is to find out the characteristics of stunting toddlers in North Luwu Regency in 2023.The research design used is descriptive research. The population in this study were toddlers in North Luwu Regency in 2023. The sample for this study was 67 toddlers and was taken using the Purposive Sampling. The data collection method uses secondary data which is then analyzed using a frequency test. The result of the research is, characteristics of stunting toddlers in North Luwu Regency in 2023 there were 39 toddlers (58.2%) male, normal birth length for 48 toddlers (71.6%), normal birth weight for 54 toddlers ( 80.6%), history of exclusive breastfeeding for 50 toddlers (74.6%), history of complete basic immunization for 64 toddlers (95.5%), history of disease no for 66 toddlers (98.5%), and history of CED pregnancy for 64 mothers (95.5%).The conclusion is, the most characteristics of stunted toddlers obtained were male, normal birth length, normal birth weight, had a history of exclusive breastfeeding, a history of complete basic immunization, no history of disease, and his mother had no history of CED pregnancy.